2011
DOI: 10.18388/abp.2011_2246
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of aqueous extract of Aframomum melegueta on ethanol-induced toxicity in rats.

Abstract: In recent years there have been remarkable developments in the prevention of diseases, especially with regards to the role of free radicals and antioxidants. Ethanol-induced oxidative stress appears to be one mechanism by which ethanol causes liver injury. The protective effect of aqueous plant extract of Aframomum melegueta on ethanol-induced toxicity was investigated in male Wistar rats. The rats were treated with 45 % ethanol (4.8 g/kg b.w.t.) for 16 days to induce alcoholic diseases in the liver. The activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Anticancer properties of this plant have been studied both in vivo on mice and more rarely in vitro on tumor cell lines (32,33). On the other hand, E. speciosa and A. melegueta species have shown antifungal, antiinflammatory, antibacterical, gastro-protective and fertilizing effects (34)(35)(36). However, no report has been clearly focused on their antitumoral properties.…”
Section: Discussionmentioning
confidence: 99%
“…Anticancer properties of this plant have been studied both in vivo on mice and more rarely in vitro on tumor cell lines (32,33). On the other hand, E. speciosa and A. melegueta species have shown antifungal, antiinflammatory, antibacterical, gastro-protective and fertilizing effects (34)(35)(36). However, no report has been clearly focused on their antitumoral properties.…”
Section: Discussionmentioning
confidence: 99%
“…High doses of ethanol (binge treatments) have been used to test the hepatoprotective effects of phytotherapeutics (Chotimarkorn and Ushio, 2008; Hu et al, 2010; Nwozo and Oyinloye, 2011; Wang et al, 2012). In addition, allyl alcohol is a liver toxicant that has occasionally been used in mice to study the effect of plant extracts (Remirez et al, 1997).…”
Section: Non-acetaminophen Models Of Hepatotoxicitymentioning
confidence: 99%
“…However, oxidative stress still could occur due to an excess production of ROS and/or a defect of antioxidant molecules, which could cause damage to macromolecules such as DNA, proteins, and lipids. Accumulating evidence has demonstrated that oxidative stress plays a critical role in the initiation and progression of a variety of liver disorders (Medina & Moreno-Otero, 2005), and many natural antioxidants have been tried to prevent oxidative stressmediated liver injury (Hewawasam et al, 2003;Nwozo & Oyinloye, 2011;Skinner & Rangasami, 2002;Srivastava & Shivanandappa, 2006). The main advantage of nature compounds or extracts is their mild action in comparison to chemically synthesized drugs.…”
Section: Introductionmentioning
confidence: 99%